After the program is over: Exploring teams and application - Judith M. Ottoson (Adult Education Research Conference, 1996)
This study found no significant association between extent of post-training application among those who attended training in teams, with others but not as a team, or alone. Unless teams are considered in the planning, teaching, and evaluation of training, as well as given follow-up support, resources, authority, opportunity, and encouragement, separate team effects are unlikely.